IN-VIVO ANALYSIS OF GRAPE SEED EXTRACT: ITS EFFECTS ON HUMAN HEALTH AND DISEASE PREVENTION (International Journal of Food and Nutritional Sciences, 2022)
The powerful bioactive chemicals found in grape seed extract (GSE), especially proanthocyanidins, have attracted a lot of interest because of the anti-inflammatory, anti-carcinogenic, and antioxidant effects they have. This review delves at the potential of GSE in illness prevention and its impacts on human health when tested in living organisms. Research on both animals and humans has shown promising results in the treatment of cancer, metabolic illnesses, cardiovascular disease, and neurodegenerative disorders. One possible mediator of inflammation and the development of MeSrelated diseases is GSPE's ability to reduce oxidative damage. Before we can go further into studying the effects of GSPE in humans, we need additional well-designed animal trials with standardised doses and GSPE composition to better understand the cause-effect link. To round up our knowledge of GSE's therapeutic uses, we go into its safety profile and bioavailability.